Peran Sistem Informasi Manajemen dalam Pengambilan Keputusan Organisasi - Amrisyah Putri Amanda Pasaribu; Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the role of Management Information Systems (MIS) in the organizational decision-making process. MIS serves as a vital tool in supporting the effectiveness and efficiency of decisions made by managers and organizational leaders. Using a qualitative approach, this research employs a case study at a government institution to illustrate how MIS contributes to the quality of information used in decision-making. The results show that a well-implemented MIS can enhance the speed, accuracy, and relevance of data in the decision-making process. Management Information Systems provide accurate and timely information needed to facilitate decision-making and problem-solving processes, enabling the functions of planning, control, and operations to run effectively. This scientific paper uses a qualitative approach with a descriptive method. The findings indicate that the development and management of MIS within an organization can lead to decisions that are not only fast and accurate but also aligned with best practices in an effective and efficient manner. Information has become a crucial resource in managing organizations.